GLOBAL ELDER ABUSE: A MEGA-MAP OF SYSTEMATIC REVIEWS. (20th December 2022) - Estenson, Lilly; Marnfeldt, Kelly; Yon, Yongjie; Mikton, Christopher; Wilber, Kathleen
Abstract: Elder abuse is an increasingly prevalent public health problem that requires a global political and evidence-based response. To make global evidence on elder abuse easier to locate and analyze, we constructed a mega-map – an interactive map that systematically identifies and overviews existing systematic reviews – on elder abuse prevalence, consequences, risk and protective factors, and interventions. Following Campbell Collaboration methodological guidelines, we conducted a comprehensive database and grey literature search of the global elder abuse literature (n=2, 776) to identify systematic reviews that examine one or more of these four abuse domains among adults age 60+ (n=111). We then coded the reviews to identify key characteristics, including the types of abuse, settings, World Health Organization (WHO) geographic regions, and demographic subgroups represented in each review, that can be filtered in the mega-map. We also adapted the Joanna Briggs Institute Critical Appraisal Checklist for Systematic Review and Research Syntheses to appraise the quality of each review. We found that the focus of existing evidence syntheses is most commonly interventions (n=59), followed by prevalence (n=52), risk factors (n=51), consequences (n=31), and protective factors (n=16). The majority of published elder abuse studies have been conducted in the European, Western Pacific, and Region of the Americas WHO geographic regions. Few reviews examine systemic abuse and system-level interventions. Future studies on elder abuse should address these gaps in research on protective factors and systemic aspects of elder abuse, and build evidence about elder abuse in the African, South-East Asian, and Eastern Mediterranean WHO geographic regions.